ChemInform Abstract: NHC‐Mediated Enantioselective Formal [4 + 2] Cycloadditions of Alkylarylketenes and β, γ‐Unsaturated α‐Ketocarboxylic Esters and Amides. Issue 36 (15th August 2013) - Leckie, Stuart M.; Brown, T. Bruce; Pryde, David; Lebl, Tomas; Slawin, Alexandra M. Z.; Smith, Andrew D.
Abstract Chiral N‐heterocyclic carbenes promote the asymmetric formal [4 + 2] cycloaddition of alkylarylketenes with β, γ‐unsaturated α‐ketocarboxylic esters and amides.